Frequency of the multi and extensively drug-resistant Salmonella Typhi in a health care facility (Journal of Fatima Jinnah Medical University, 2023)
Background: Antibiotic resistance is increasing against Salmonella Typhi (S. Typhi), causative agent of enteric fever, at a very high pace in Pakistan. The objective of this study was to evaluate the emergence of multi and extensively drug resistant Salmonella Typhi among suspected patients in a public health care facility in Lahore.Patients and methods: 5cc blood samples from the patients with high grade fever (>38°C), vomiting and bradycardia (heart rate 84 bpm) were collected from laboratory of Arif Memorial Teaching Hospital, Lahore over six months (August 2020-January 2021), After informed consent, questionnaire were filled and total 97 samples were taken from suspected patients and screened for Salmonella Typhi by using Typhidot IgG/IgM by ELISA kit (one step typhoid fever) for S. Typhi. Gram staining, culture and biochemical testing was performed for confirmation. Antibiotic susceptibility testing was used to evaluate the emergence of antibiotic resistance. Statistical analysis was performed by using SPSS 20.0, software. Chi square test was used,Results: Total 55 (56.7%) samples out of 97 (100%) were reported positive for Salmonella Typhi. Antimicrobial susceptibility testing results indicated that 6 samples were resistant to more than one antibiotic commonly called as multidrug resistant, 44 samples were extensively drug resistant and 5 samples were nonresistant/sensitive to selected antibiotics. Highest resistance was reported against Ampicillin (51 samples (92.7%) and Co-trimoxazole (50 samples (90%)). Resistance against Moxifloxacin and Tobramycin, Ciprofloxacin, Ceftriaxone Cefuroxime and Cefotoxime, Cefxime, Levofloxacin, Salbactum, Imepenum and Amikain was 47 (85.4%), 46 (83.6%), 45 (81.81%), 44 (80%), 37 (67.2%), 32 (58.18%), 14 (45%) and 9 (16.3%) respectively. Lowest resistance was reported against Meropenum 5 (9%) and Azithromycin 1 (1%).Conclusion: It is concluded that the monitoring of MDR and XDR must be performed by all clinical microbiology/pathology laboratories to implement effective measures to reduce the emergence of antimicrobial resistance.
Keywords: Multidrug resistant (MDR), Extensively drug resistance, Enteric fever, Salmonella typhi.